Perovskite materials for multi-junction solar cell applications - McMeekin, D (2018)
The work presented in this thesis will describe studies on organic-inorganic perovskite materials when being used in tandem and multi-junction solar cell architectures. Perovskite solar cells (PSC) have recently emerged as a viable absorber material for photovoltaic applications, owing to its remarkable optoelectronic properties along with its ease of fabrication. These attributes have led to a rapid progress in device performance, where over the last few years, perovskite solar cells have reached efficiencies that other solar technologies took decades to achieve. Moreover, one unique economic advantage of this technology is its ability to offer solution-processible fabrication. This characteristic enables perovskites to be applied to existing large-scale deposition techniques on rigid or flexible substrates such as roll-to-roll (R2R) processing, blade coating or inkjet printing techniques. These large area film manufacturing techniques have the promise of drastically lowering solar cell fabrication costs and thus transforming the global energy landscape. By offering an affordable and renewable energy source to satisfy our ever-increasing energy needs, the emerging perovskite solar technology can help lead the fight against climate change. Initially, the work presented in chapters 1 and 2 will serve as an introduction to the theory, background and motivation for the investigation of perovskite solar cells in multi-junction solar cell applications. We also discuss the difficulties encountered by the research community when attempting to design and fabricate a perovskite material suitable for tandem and multi-junction applications. We present in chapter 3 the experimental methods used throughout the thesis. In chapter 4, we introduce a perovskite system that is suitable for tandem applications with c-Si solar cells. This highly crystalline and efficient formamidinium-cesium mixed-cation lead mixed halide [HC(NH2)2](1-x)CsxPb(I(1-y)Bry)3 exhibits improved thermal and photo-stability over the conventional methylammonium lead mixed halide perovskite CH3NH3Pb(Br(1-y)Br(1-y))3. By combining a 1.74 eV [HC(NH2)2]0.83Cs0.17Pb(I0.6Br0.4)3 perovskite material with a crystalline silicon (c-Si) solar cell, we demonstrated a highly efficient 4-terminal tandem architecture. This paved the way for perovskite materials to be utilized in tandem application with the established c-Si. Chapter 5 will discuss the crystallization kinetics and the control of morphology of this formamidinium-cesium mixed-cation lead mixed-halide perovskite system. We show that colloids, present in the precursor solution in the form of lead polyhalides: [PbX3]1-, [PbX4]2-, [PbX5]3-, [PbX6]4-, can serve as nucleation centers and impact the final morphology and optoelectronic properties of the perovskite film. Highly crystalline perovskite material with low electronic disorder and long-lived carrier lifetimes can be obtained through careful consideration of the precursor solution. Finally, in chapter 6, we demonstrate fully solution-processed monolithic all-perovskite tandem and triple-junction solar cells. The ability to sequentially process a perovskite layer on top of underlying perovskite layers opens new possibilities for large scale manufacturing of multi-junction perovskite solar cells. The work presented in this thesis demonstrates the feasibility of using perovskite materials as an absorber in tandem and multi-junction solar cell applications.